Market level assessment report: Fruits and vegetables intake Vietnam and Nigeria – Vietnam report - Hernández, Ricardo; Hoang, My Lan; Tran, Hieu (2021)
The research described in this document is part of the FVN project: “Fruits and Vegetables intake in Vietnam and Nigeria’. This project addresses the problem of the triple burden of malnutrition among low-income urban populations in Nigeria and Vietnam by increasing intake of fruits and vegetables through food system innovations that improve access through the diversification of retail outlets, enhance affordability through a client-specific coupon system, and boost acceptability of fruits and vegetables through promotional campaigns involving public and private stakeholders and civil society organizations.